2018
DOI: 10.1039/c8nr01210e
|View full text |Cite
|
Sign up to set email alerts
|

Field dependence of the ferromagnetic/superconducting proximity effect in a YBCO/STO/LCMO multilayer

Abstract: The interaction between superconductivity and magnetism in spatially confined heterostructures of thin film multilayers is investigated in the ferromagnetic manganite La2/3Ca1/3MnO3 (LCMO) and the high-temperature superconductor YBa2Cu3O7-δ (YBCO) mediated by an intermediate insulating SrTiO3 (STO) layer. The STO layer is used to mediate and tune the range of interactions between the ferromagnet and superconductor. A magnetically depleted layer with zero-magnetisation within the LCMO layer is shown by polarise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 38 publications
0
23
0
Order By: Relevance
“…We note also that the system's properties and evidences at hand do not suggest that other long-range "proximity" scenarios, such as for example the giant proximity effect observed in all oxide YBCO/SrTiO 3 /La 2/3 Ca 1/3 MnO 3 (Refs. 35,36 ) could be responsible of our experimental observations. On the other hand, the effect of the stray field of the SC flux is robust towards details of the magnetic structure of the interface.…”
Section: Discussionmentioning
confidence: 77%
“…We note also that the system's properties and evidences at hand do not suggest that other long-range "proximity" scenarios, such as for example the giant proximity effect observed in all oxide YBCO/SrTiO 3 /La 2/3 Ca 1/3 MnO 3 (Refs. 35,36 ) could be responsible of our experimental observations. On the other hand, the effect of the stray field of the SC flux is robust towards details of the magnetic structure of the interface.…”
Section: Discussionmentioning
confidence: 77%
“…It is also well established that the penetration of spin-singlet SC order parameter into a FM is highly damped by the presence of a ferromagnetic exchange field at the interface and hence is very short ranged. , Studies have shown that high-temperature SCs, such as YBa 2 Cu 3 O 7−δ (YBCO), in close proximity to a half-metallic perovskite oxide FM, such as La 0.67 Ca 0.33 MnO 3 (LCMO), , La 0.67 Sr 0.33 MnO 3 (LSMO), and so forth, may modify the interfacial magnetization in the FM over considerably larger length scales. Moreover, the emergence of magnetic phases such as the induced magnetically dead/depleted (MD) layer and magnetization reversal, in the FM layer near the interface, has been observed even when the FM and the SC layers are separated by a thin insulating (I) spacer layer in the so-called tunnelling geometries as in YBCO/SrTiO 3 (STO)/LCMO and YBCO/STO/LSMO heterostructures. This proximity effect over larger length scales in these heterostructures is attributed to the formation of spin-triplet Cooper pairs in the SC due to the inhomogeneous exchange field near the interfaces…”
Section: Introductionmentioning
confidence: 99%
“…Because the magnetic proximity effect (MPE) is essentially concentrated in a very small volume near the interfaces of heterostructures, it is highly sensitive to the structural, chemical, and electronic properties of the interfaces. The polarized neutron reflectivity (PNR) technique has been used to study MPE in FM/SC and FM/I/SC systems, employing models with an emergent interfacial MD layer (i.e., reduced magnetic moments in the interfacial LSMO layer). Recently, using PNR, , the effect of structural changes on the proximity effect was observed on the irradiated MgO­(substrate)/YBCO/STO/LSMO heterostructures, where a reduction in the proximity effect was observed . This was attributed to a suppressed SC of YBCO due to irradiation-induced structural changes.…”
Section: Introductionmentioning
confidence: 99%
“…Among these methods, the interaction of the superconductor (SC) with a ferromagnet (FM) leads to very interesting results [ 16 , 17 , 18 ]. If the superconductor and the ferromagnet are in direct contact, coupling phenomena such as proximity [ 19 , 20 , 21 , 22 ] and inverse proximity effects [ 23 ], spin-orbit [ 24 ], or dipolar coupling [ 25 , 26 ] can take place. For power applications, to eliminate the unwanted proximity effects [ 27 ] and increase the J c a thin barrier layer is introduced at the SC/FM interface [ 28 ].…”
Section: Introductionmentioning
confidence: 99%